Sensory Characteristics and Consumer Liking of Basil Syrups ( Ocimum basilicum L.) in Different Sensory Settings - Ervina Ervina; Kyle Bryant; Dwi Larasatie Nur Fibri; Wahyudi David (Polish Journal of Food and Nutrition Sciences)
The objective of this study was to investigate the sensory profiles of basil syrups formulated with different contents of basil leaf extract and sugar, and to determine the key attributes of consumer liking. Moreover, this study also measured consumers’ perceptions in two sensory evaluation settings of blind and non-blind (informed) tests. Sixty adult consumers were involved in the evaluation. The basil leaf extract and sugar contents influenced the sensorial characteristic of basil syrups. Moreover, consumers had different perceptions and changed their preferences for this product in different sensory evaluation settings. Information related to ingredients and sugar contents was demonstrated to consumers to enable the shift in their preferences. Consumers perceived the basil syrups as significantly healthier in the non-blind setting ( p <0.001) compared to the blind test ( p =0.110). Moreover, the liking showed to be significantly higher in the non-blind setting compared to the blind test ( p=0.050), especially for the sugar-free samples. This research could be used as a preliminary study to further develop functional drinks made from basil leaves and to consider the information regarding food ingredients provided to consumers.